Information Systems Management Issues for the 1990s - Niederman, Fred; Brancheau, James C.; Wetherbe, James C. (MIS Quarterly, 1991)
This three-round delphi survey of senior IS executives is the third in a series designed to determine the most critical issues in IS management. Analysis focuses on respondents’ assessments of specific issues as well as emerging trends. Key findings include: (1) Continued concern for traditional issues such as strategic planning and organizational alignment; (2) only six of the top issues from 1936 remained in the top 10; (3) one new issue, technology infrastructure, made the top 10; (4) three issues from previous studies rejoined the top 10—IS human resources, software development, and telecommunication systems; and (5) data-related issues now occupy the top two slots. This study reveals two important trends as the field enters the 1990s. First is the rising importance of technology infrastructure issues. Technology infrastructure issues now occupy three of the top 10 slots including the highest position. Second, it appears that internal effectiveness issues have made a strong comeback after being virtually ignored in 1986. IS human resources, software development, and the applications portfolio—issues that make up the core of the IS function—all increased in importance.